Unexpected decrease of full-length prion protein in macaques inoculated with prion-contaminated blood products - Jaffré, Nina; Delmotte, Jérôme; Mikol, Jacqueline; Deslys, Jean-Philippe; Comoy, Emmanuel (Frontiers in Molecular Biosciences, 2023)
The presence of prion infectivity in blood from patients affected by variant of Creutzfeldt-Jakob disease (v-CJD), the human prion disease linked to the bovine spongiform encephalopathy (BSE), questions the risk of inter-human transmission of this fatal prion disease through transfusion. In the frame of various experiments, we have previously described that several cynomolgus macaques experimentally exposed to prion-contaminated blood products developed c-BSE/v-CJD, but the vast majority of them developed an unexpected, fatal disease phenotype focused on spinal cord involvement which does not fulfill the classical diagnostic criteria of v-CJD. Here we show that extensive analyses with classical current techniques failed to detect any accumulation of abnormal prion protein (PrPv-CJD) in the CNS of these myelopathic animals, i.e. the biomarker considered as responsible for neuronal death and subsequent clinical signs in prion diseases. Conversely, in the spinal cord of these myelopathic primates we observed an altered pattern of their physiological cellular PrP pattern: PrP was not detectable under its full-length classical expression but mainly under its physiological terminal-truncated C1 fragment. This observed disappearance of the cellular PrP N-terminal fragment at the level of the lesions may provide a first experimental evidence from a link between loss-of-function of the cellular prion protein and disease onset. Whatever, this original prion-induced myelopathic syndrome suggests an unexpected wide extension of the domain of the prion diseases, that is up to now restricted to pathologies associated to abnormal modifications of the cellular PrP towards highly structured conformations.